2023
DOI: 10.3390/md21020057
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Skin Hydrating Efficacy of Fish Collagen from Greenland Halibut as a High-Value Active Ingredient for Cosmetic Applications

Abstract: The industrial processing of fish for food purposes also generates a considerable number of by-products such as viscera, bones, scales, and skin. From a value-added perspective, fish by-products can act also as raw materials, especially because of their collagen content (particularly in fish skin). Interestingly, the potential of marine collagen for cosmetic applications is enormous and, remarkably, the extraction of this protein from fish skins has been established for different species. Using this approach, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
0
7
0
1
Order By: Relevance
“…Compared with type A and type B commercial gelatins, the results showed that gelatin extracted from Greenland halibut skin has an identical profile to commercial type B gelatin ( Figure 3 , green line) [ 46 ]. In the present study, the CD spectrum of gelatin exhibits a marked decrease in the negative intensity around 200 nm, which is characteristic of proteins with a random coil [ 47 , 48 , 49 ]. In addition, the slight CD-peak around 220 nm appears in the negative part of the graph, which could indicate the development of chain reversals in the peptide chains after the destruction of the triple helical structure [ 23 , 50 ].…”
Section: Resultsmentioning
confidence: 69%
“…Compared with type A and type B commercial gelatins, the results showed that gelatin extracted from Greenland halibut skin has an identical profile to commercial type B gelatin ( Figure 3 , green line) [ 46 ]. In the present study, the CD spectrum of gelatin exhibits a marked decrease in the negative intensity around 200 nm, which is characteristic of proteins with a random coil [ 47 , 48 , 49 ]. In addition, the slight CD-peak around 220 nm appears in the negative part of the graph, which could indicate the development of chain reversals in the peptide chains after the destruction of the triple helical structure [ 23 , 50 ].…”
Section: Resultsmentioning
confidence: 69%
“…Currently, the research of collagen extracted from marine organisms for tissue engineering biomaterials mainly focuses on marine fish, jellyfish, sponges, etc. These aquatic organisms’ skin, muscles, and cartilage tissue are rich in collagen [ 20 , 21 ]. Collagen of marine origin is not only similar to traditional terrestrial mammalian collagen in terms of amino acid composition and biocompatibility, but also has greater advantages than mammalian collagen in terms of vast sources, easy extraction, absence of pathogenic microbial contamination, and stable chemical and physical properties—especially in the fish processing industry and fishing activities [ 22 ].…”
Section: Collagenmentioning
confidence: 99%
“…1,2 Despite being extracted from natural sources, this polymer has other advantageous properties, such as its low toxicity, weak antigenicity, high nutritional value, and exibility, as well as its biodegradability and biocompatibility. 3,4 Its extraction from mammalian sources, i.e., bovines, is decreasing due to health and environmental problems, 5 and, therefore, sh has become a good alternative collagen source. In fact, the decrease in collagen extraction in land animals can be explained by the possible human infections resulting from the outbreak of diseases in stock animals.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Despite being extracted from natural sources, this polymer has other advantageous properties, such as its low toxicity, weak antigenicity, high nutritional value, and flexibility, as well as its biodegradability and biocompatibility. 3,4…”
Section: Introductionmentioning
confidence: 99%